Effect of quality metric monitoring and colonoscopy performance - Razzak, Anthony; Smith, Dineen; Zahid, Maliha; Papachristou, Georgios; Khalid, Asif (Endoscopy International Open, 2016)
Background and aims: Adenoma detection rate (ADR) and cecal withdrawal time (CWT) have been identified as measures of colonoscopy quality. This study evaluates the impact of monitoring these measures on provider performance.Methods: Six blinded gastroenterologists practicing at a Veterans Affairs Medical Center were prospectively monitored over 9 months. Data for screening, adenoma surveillance, and fecal occult blood test positive (FOBT +) indicated colonoscopies were obtained, including exam preparation quality, cecal intubation rate, CWT, ADR, adenomas per colonoscopy (APC), and adverse events. Metrics were continuously monitored after a period of informed CWT monitoring and informed CWT + ADR monitoring. The primary outcome was impact on ADR and APC.Results: A total of 1671 colonoscopies were performed during the study period with 540 before informed monitoring, 528 during informed CWT monitoring, and 603 during informed CWT + ADR monitoring. No statistically significant impact on ADR was noted across each study phase. Multivariate regression revealed a trend towards fewer adenomas removed during the CWT monitoring phase (OR = 0.79; 95 %CI 0.62 – 1.02, P = 0.065) and a trend towards more adenomas removed during the CWT + ADR monitoring phase when compared to baseline (OR = 1.26; 95 %CI 0.99 – 1.61, P = 0.062). Indication for examination and provider were significant predictors for higher APC. Provider-specific data demonstrated a direct relationship between high ADR performers and increased CWT.Conclusions: Monitoring quality metrics did not significantly alter colonoscopy performance across a small heterogeneous group of providers. Non-significant trends towards higher APC were noted with CWT + ADR monitoring. Providers with a longer CWT had a higher ADR. Further studies are needed to determine the impact of monitoring on colonoscopy performance.